Perempuan dalam Representasi Legislatif Daerah Kabupaten Kerinci 2004-2014 - Elga Nokia; Herwandi Herwandi; Midawati Midawati (Analisis Sejarah, 2025)
The Legislative Elections of Kerinci District in the 2004-2024 period indicate that women's representation in the legislature remains limited, despite the fact that the number of female voters is higher than male voters, and the 30% quota for female candidates has been met. However, the number of elected female candidates is still far from expectations. The aim of this study is to examine the struggles of female legislative candidates, both those who were elected and those who were not, in their efforts to become members of the legislature. The research method used historical methods. To analyze the struggles of female candidates, political participation theory, which explains the involvement of individuals or groups in the political process, and political mobilization theory, which focuses on efforts to encourage individuals to participate in politics, are applied. The study shows that female representation in the politics of Kerinci Regency still faces many challenges and does not reflect true political participation. Women are often treated as mere fillers for the 30% quota without sufficient support from political parties. Economic resource limitations and low party support hinder their campaigns and make it difficult to build political networks. The research findings reveal that women’s representation tends to be symbolic. Female candidates are often included merely to fulfill the quota, without meaningful support from political parties, particularly regarding strategic list placement and access to political resources. Economic constraints, patriarchal culture, and low self-confidence reinforce male dominance in the local political structure. These findings affirm that women’s participation is hindered by structural barriers and ineffective mobilization. Therefore, political party reform and cultural transformation are essential to ensure equal participation opportunities for women in politics.